PENGARUH PELATIHAN, DISIPLIN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA BAITUL MAAL WA TAMWIL INDRAGIRI RENGAT - Lisa Dwi Anggraini; Rosnelly Roesdy; Anggia Paramitha (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2025)
Baitul Maal Wat Tamwil (BMT) is a Sharia-based microfinance institution thatfunctions to collect public funds, provide financing for micro, small, and medium enterprises(MSMEs), and manage social funds such as zakat, infaq, and sadaqah. The existence of BMTplays a vital role in supporting the economy of the Muslim community.This study aims toanalyze the influence of training, work discipline, and job satisfaction on employeeperformance at Baitul Mal Wa Tamwil (BMT) Indragiri Rengat. The research problem arisesfrom fluctuating employee performance, as reflected in attendance records, achievement ofwork targets, and interviews indicating relatively low job satisfaction. The study employs aquantitative approach using a survey method with questionnaires. The population consists ofall 34 employees of BMT Indragiri Rengat, and the sampling technique used is total sampling.Data were analyzed using multiple linear regression, including validity, reliability, classicalassumption tests, t-test, F-test, and the coefficient of determination.Keywords: Training, Work Discipline, Job Satisfaction, Employee Performance